Applying effective feedback principles to promote the ethics of care and justice during emergency remote teaching and learning in three chemical engineering modules - Rishen Roopchund; Vizelle Naidoo (University of Johannesburg, 2023)
The COVID-19 pandemic lockdown disrupted higher education practices and forced students and lecturers to rapidly migrate to emergency remote teaching and learning (ERT&L). Initially, ERT&L robustly focused on teaching and assessment to complete syllabi, without fully considering care and justice to students who were no longer consolidated in one location.  During the lockdown, students were exposed to socio-economic plights, and mental health challenges, among others. Hence, this article aimed to consider how the pedagogical tool of effective feedback could promote the ethics of care and justice to support students during ERT&L. The feedback practices implemented during the lockdown were maintained after contact lectures resumed, and their effects were quantified to determine the overall impacts on optimizing T&L and ensuring a conducive learning environment- regardless of whether T&L occurs at university or remotely. Effective feedback practices, recommended by the literature, were applied by two lecturers within three undergraduate chemical engineering modules. Lecturer 1 adopted a blended learning approach in modules 1 and 2 before the lockdown, while lecturer 2 functioned as a full contact module. A quantitative research approach was adopted in which module and teaching evaluations were used to quantify the effects of the feedback interventions on T&L in the three modules. The results indicated an overall positive effect, with significant student satisfaction with the feedback interventions adopted from the literature to promote the ethics of care and justice during ERT&L. Based on the methodology and results, an empirical model is proposed to optimize any pedagogical intervention that education practitioners may strive to use to improve their assessment practices.